Health library for patients in general practice. Issue 6416 (18th February 1984) - Varnavides, C K; Zermansky, A G; Pace, C
Abstract : We describe the establishment of a health lending library for patients in a suburban general practice. The library is housed in the surgery waiting room and comprises 413 books and 35 audio tapes on topics related to health. Analysis of the first year's use showed 703 borrowings (677 books and 26 audio cassettes). Borrowers ranged the spectrum of social class and educational status but women predominated, and borrowers included many who admitted that they seldom read books. Most borrowings were opportunistic, though some were planned by the patient and a few recommended by a health care professional. Most readers claimed to have learned from their reading and to have found their reading useful. We think that a health library is a useful tool of primary care, particularly for prevention.